Hygiene and Sanitation of Food Processing Center in Gudang 100 Warehouse at Tanjung Perak Sea Port of Surabaya 2018 - Tifal - Dakwani (Universitas Airlangga, 2019)
Food Processing Premise is a place for processing food raw ingredients to become ready to consume food. In order to function optimally, the premises are needed to be controlled frequently particularly in the port area where many visitors and staffs are in needs of health protection during their activities in this area. For this purpose, the authority has been attempting to increase and maintain food and baverage quality in this area therefore it could avoid any public health menaces from food contamination and intoxication for the population. As basic health survey (RISKESDAS) in 2013 reported diseases contributed as public health threats such as diarrhea 3.5%, typhoid 2.2%, hepatitis 1.2% (Riskesdas, 2013). The study aims to analyse the hygiene and sanitation implementation of food processing center in Gudang 100 warehouse at Tanjung Perak Sea Port of Surabaya. This present study is an observational study with cross sectional design. The sample was obtained based on 2017 data and mapping of 60 food tenant premises. 5 places were observed during study period. The variables observed were including of location, building, sanitation facilities, dining room, food storage, ingredients, food, the process, serving, food stuff, and the employee. The variables were observed using the total score as enacted by Indonesian Ministry of Health regulation NO.1098/MENKES/SK/VII/2003 regarding of Hygiene and sanitation standards for food stalls and restaurant. The result of the study shows there are 2 food stalls (B and C) with score <700 while the other stalls (A, D and E) reach score >700. The conclusion of this study highlights the needs of adjusting the requirement of the hygiene and sanitation of food stalls and restaurant as well as provide regular trainings for food handlers.